Tracking wireworm burrowing behaviour in soil over time using 3D X‐ray computed tomography. Issue 8 (12th March 2020) - Booth, Samuel; Kurtz, Benedikt; de Heer, Martine I; Mooney, Sacha J; Sturrock, Craig J
Abstract: BACKGROUND: Wireworms (larvae of the click beetle, Elateridae) are a significant agricultural pest, causing crop damage and reducing yields globally. Owing to the complex nature and opacity of the soil environment, research to investigate wireworm behaviour in situ has been scarce. X‐ray computed tomography (CT) has previously been demonstrated as a powerful tool to independently visualise the 3D root system architecture, macroinvertebrate movement and distribution of burrow systems in soil, but not simultaneously within the same sample. In this study, we apply X‐ray CT to visualise and quantify wireworms, their burrow systems and the root architecture of two contrasting crop species ( Hordeum vulgare and Zea mays ) in a soil pot experiment scanned at different time intervals. RESULTS: The majority of wireworm burrows were produced within the first 20 h post inoculation, suggesting that burrow systems are established quickly and persist at a similar volume. There was a significant difference in the volume of burrow systems produced by wireworms between the two crop species suggesting differences in wireworm behaviour elicited by crop species. There was no significant correlation between burrow volume and either root volume or surface area, indicating this behavioural difference is caused by factor(s) other than the mass of root systems. CONCLUSION: X‐ray CT shows potential as a non‐destructive technique to quantify the interaction of wireworms in the natural soil environment with crop roots, and aid the development of effective pest management strategies to minimise their negative impact on crop production. © 2020 Society of Chemical Industry Abstract : Wireworm behaviour is difficult to investigate due to the opaqueness of soil. This article examines the use of X‐ray computed tomography to track burrowing behaviour with future application to pest management. © 2020 Society of Chemical Industry